Interpret suffering. Walter Benjamin, Theodor Adorno and the question of truth - Moreno, María Rita (Revista de Humanidades de Valparaíso, 2021)
This article postulates that the criticality of epistemology elaborated by Walter Benjamin and Theodor W. Adorno is based not so much on the reformulation of a philosophical praxis against modern reason, but mainly on the metamorphosis of the concept of truth. Specifically, it is affirmed that the critique of modern reason carried out by both thinkers is associated with the determination of the temporal nucleus of truth as negativity and mourning. In the context of a rational crisis, Benjamin and Adorno open the possibility of a relationship with objectivity in the form of a critical interpretation of that temporal nucleus. This, linked to the dialectic of modern catastrophe, deals with exposing the fragments produced by the subjectivist super-determination governed by the logic of identity. To justify this, first, we explain the identification made by both philosophers between the temporal nucleus of truth and the concept of sad-negative truth; imbrication that tries to condense the consequences of the subjectivist constitution of reason. Then, we point out the conjugation of this definition of truth with the production of suffering. Next, we determine in what sense the negativity of the truth opens up the dialectical character of the modern catastrophe. Finally, we indicate the necessary association of such a critical epistemology with the historical apocatastasis.